Dynamics of the Implementation of Qawaid Fiqhiyyah in the Sharia Economic Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) - Imam Kamaluddin; Achmad Charis Maulana; Sultan Nanta Setia Dien Labolo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to analyze the use of fiqh rules in Islamic economic fatwas issued by the National Sharia Council-Majelis Ulama Indonesia (DSN-MUI). The research method used is library research by using 152 DSN-MUI fatwas as primary data sources. The results showed that of the 152 fatwas studied, there were 4 fatwas (3%) that did not use fiqh rules, while 148 fatwas (97%) used fiqh rules in varying amounts between 1-8 rules per fatwa. The most frequently used fiqh rules are the rules